Factors Associated with Baby Blues Syndrome among Postpartum Mothers at a Maternal and Child Hospital in Indonesia - Fauziah Botutihe; Nur Halimah; Seftiana Dewi; Alamsyah Alamsyah; Riska Riska (International Journal Of Health Science, 2026)
The postpartum period is a critical transitional phase that involves substantial physical recovery and psychological adaptation for mothers following childbirth. During this period, many women experience emotional disturbances, one of the most common being baby blues syndrome. Baby blues syndrome is characterized by mood swings, tearfulness, anxiety, irritability, and emotional instability that typically occur within the first week after delivery. Although often considered a mild and self-limiting condition, unresolved baby blues may progress into postpartum depression, leading to adverse consequences for maternal well-being, infant development, and family functioning. This study aimed to analyze factors associated with baby blues syndrome among postpartum mothers at a maternal and child hospital in Makassar, Indonesia. A quantitative analytical study with a cross-sectional design was conducted involving 50 postpartum mothers selected through purposive sampling. Data were collected using the Edinburgh Postnatal Depression Scale (EPDS) and structured questionnaires assessing occupational status, husband support, and family support. Data analysis was performed using Fisher’s Exact test with a significance level of 0.05. The findings revealed that 82% of respondents experienced baby blues syndrome. Statistically significant associations were identified between occupational status (p = 0.000), husband support (p = 0.000), and family support (p = 0.000) with the occurrence of baby blues syndrome. In conclusion, occupational and psychosocial factors play a crucial role in the development of baby blues syndrome. Strengthening family-centered support and implementing early psychological screening during the postpartum period are recommended to prevent more severe maternal mental health problems.